2015
DOI: 10.1144/jgs2015-048
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary stress orientations in the Faroe–Shetland region

Abstract: The Faroe–Shetland region of the NE Atlantic continental margin contains a number of complexly structured Mesozoic–Palaeogene-age rift basins, but in comparison with the contiguous British Isles and North Sea Basin, the state of crustal stress in the Faroe–Shetland region is poorly understood. The orientation of maximum horizontal compressional stress (σ Hmax ) across most of NW Europe is roughly NW–SE, which is considered to be controlled by forces acting at the plate boundaries. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
4
10
0
Order By: Relevance
“…half-graben basins in rift settings can trigger extensional faulting and fracturing, and may alsodemonstrates just one vague alignment orientation (corresponding to the crest of the BNS 543 structure; Fig 10). This ENE-WSW alignment of edifices contradicts the regional stress 544 orientation (NW-SE) (Holford et al 2016) and no fault pathways have been identified on the 545 seismic data (although potential faults could be obscured by the poor sub-basalt imaging). As 546 a result, we suggest that the primary influence on edifice distribution in the BNVF is the 547 inclined rheological boundaries in the subsurface strata.…”
Section: Emplacement Of Monogenetic Plumbing Systems and Influence Ofmentioning
confidence: 85%
See 1 more Smart Citation
“…half-graben basins in rift settings can trigger extensional faulting and fracturing, and may alsodemonstrates just one vague alignment orientation (corresponding to the crest of the BNS 543 structure; Fig 10). This ENE-WSW alignment of edifices contradicts the regional stress 544 orientation (NW-SE) (Holford et al 2016) and no fault pathways have been identified on the 545 seismic data (although potential faults could be obscured by the poor sub-basalt imaging). As 546 a result, we suggest that the primary influence on edifice distribution in the BNVF is the 547 inclined rheological boundaries in the subsurface strata.…”
Section: Emplacement Of Monogenetic Plumbing Systems and Influence Ofmentioning
confidence: 85%
“…390 95 Ma) (Ebdon et al 1995). The regional orientation of maximum horizontal compressional 96 stress is largely NW-SE (Holford et al 2016). The FSB is characterised by intra-basinal highs 97 (Rona, Flett, Westray and Corona ridges; Fig.…”
Section: Geological History Of the Fsb 92mentioning
confidence: 98%
“…Plate break-up adjacent to the Faroe -Shetlandnorth Rockall area was complex and protracted, and included the separation and rotation of the Jan Mayen microcontinent; this may have generated stresses that contributed to the concentration of compressional structures in that area (Stoker et al 2013). Borehole breakouts in the Faroe-Shetland Basin indicate that the contemporary maximum horizontal compressive stress is orientated approximately NW-SE in the northern part of the basin, but that more variable stress orientations occur in its central and SW parts, and these have been interpreted in terms of deflections towards weak faults (Holford et al 2016). This is compatible with the basin-parallel trends of compressional structures in the north of the basin, and variable trends of the Judd and Westray anticlines in the south.…”
Section: Discussionmentioning
confidence: 99%
“…The orientation of the UK and UKCS stress field has been studied extensively (Williams et al, 2015(Williams et al, , 2018Holford et al, 2016;Kingdon et al, 2016;Fellgett et al, 2017b)). Kingdon et al (2016) reported that the orientation of S HMax across the UK landmass is 150.9°± 13.1°, which is the result of ridge-push forces associated with the Mid Atlantic Ridge (Klein and Barr, 1986;Gölke and Coblentz, 1996).…”
Section: Orientation Of the Uk Stress Fieldmentioning
confidence: 99%
“…The latest edition of the World Stress Map (WSM) includes all of the current openly available stress data for the UK (Heidbach et al, 2016) which has been greatly expanded by recent studies (Williams et al, 2015(Williams et al, , 2018Holford et al, 2016;Kingdon et al, 2016). Information from the WSM has previously been used to estimate stress magnitudes .…”
Section: Introductionmentioning
confidence: 99%